Analysis of the Commitment of Organizations and Government Internal Control Systems to Fraud Prevention in the Government Sector - Zainul Arifin; Fathurrahman Fathurrahman (Budapest International Research and Critics University, 2022)
The purpose of this study was to analyze and examine the effect of organizational commitment and the government's internal control system on fraud prevention in the government sector. In this study, the respondents were the Auditors of the Supreme Audit Agency (BPK) of the Republic of Indonesia. Sampling was done by using the sampling method, with the number of samples collected as many as 148 respondents. The type of data used in this research is primary data. The data collection method in this study used a questionnaire distributed via google form. The results of the research and analysis state that organizational commitment and the government's internal control system have a significant effect on fraud prevention in the government sector, especially in the Supreme Audit Agency (BPK) of the Republic of Indonesia. The data analysis technique used in this research is the application of the Partial Least Square model estimation application with the smartPLS statistical software version 3.3.6 for Windows 64-bit.